Distance Learning: Challenges and Opportunities in the Context of Language Learning in Higher Education - Bimas Reskiawan; Made Ayu Anggreni; Nurmadina Hs; Dahlan Abdullah (International Journal of Language and Ubiquitous Learning, 2023)
Background. Distance learning has become a major focus in the higher education context, especially in line with digital transformation and the global pandemic. The background to this change creates the need to understand students' perceptions of distance learning, especially in language learning at Indonesian universities. Purpose. This research aims to contribute to the development of a better learning system through a quantitative approach with survey methods. The aim of this research is to analyze student perceptions of distance learning and identify factors that can increase its effectiveness. Method. This research methodology adopts a quantitative study design with a survey approach. The research objects are language students at various universities in Indonesia. The research sample consisted of 30 respondents selected purposively, covering various demographic characteristics. Data collection was carried out through a questionnaire distributed via Google Forms, allowing participation of students from various geographic areas. Results. The research results showed that although students felt ready for distance learning, there were concerns regarding inequalities with face-to-face learning. The main challenges involve limited internet connections and communication difficulties. However, opportunities arise through easy access to materials and independent development of skills. Data analysis focuses on the interpretation of results, highlighting the importance of technological infrastructure and more effective communication strategies. Conclusion. The conclusion of this research is that a deeper understanding of student perceptions of distance learning can provide a foundation for improving learning experiences and effectiveness in the future. By understanding the challenges and opportunities students face, educational institutions can direct their efforts towards necessary updates and improvements, so that distance learning can provide a more meaningful and equivalent experience to face-to-face learning.